2016
DOI: 10.1038/nphoton.2016.188
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Power conversion efficiency exceeding the Shockley–Queisser limit in a ferroelectric insulator

Abstract: In the version of this Article originally published, in Fig. 3a, the units on the left-hand y axis were incorrect; they should have read '(A cm © 2 0 1 6 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…Each bandgap corresponds to an S–Q limit. The bandgap of 1.34 eV gives the largest possible S–Q limit of 33.7% . Research into photovoltaic materials strives to approach as closely to this limit as possible.…”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
See 4 more Smart Citations
“…Each bandgap corresponds to an S–Q limit. The bandgap of 1.34 eV gives the largest possible S–Q limit of 33.7% . Research into photovoltaic materials strives to approach as closely to this limit as possible.…”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…In addition, the ABO 3 perovskites have shown a widely tunable range of bandgaps (1.1–2.0 eV) which are suitable for visible light absorption and harvesting . More recently, it has been found that an ABO 3 perovskite—BTO—is able to exhibit a η photo which exceeds the S–Q limit despite the fact that the bandgap of BTO is greater than 3 eV so that less than 10% of the energy in the solar spectrum is absorbed . This is because the bulk photovoltaic effect (BPVE) in noncentrosymmetric crystals, e.g., tetragonal BTO, results from the photoexited nonthermalized electrons losing their energy and descending to the bottom of the band .…”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
See 3 more Smart Citations